HUBUNGAN KESEIMBANGAN JUMLAH UANG BEREDAR TERHADAP INFLASI DI INDONESIA PERIODE 1998-2018 - Dewi Mahrani Rangkuty (JEP (Jurnal Ekonomi Pembangunan), 2020)
This research aims to analyze how the balance of money supply to the inflation in Indonesia period is 1998-2018. Using the data time series from 1998 to 2018 sourced from Bank Indonesia, the research method used is the Error Correction Model (ECM). The results showed that there was a long-term balance relationship between inflation and the sum of the money supply over the period from 1998 to 2018. Inflation will decline over the next period to correct the short-term balance mistakes over the long term and the money supply has a positive and significant impact on inflation for 1998-2018. The increasing amount of money supply will have an impact on high inflation. Bank Indonesia as a monetary authority can suppress the rate of inflation by controlling the amount of money circulating in the community at any period to maintain the stability of the price of goods and services in the market.